A Proactive-based Malware Detection Approach for Android Smartphone - Dr. K. Muthmanickam, Dr. P. C. Senthil Mahesh, Dr. S. Hemalatha (International Journal of Advanced Science and Technology, 2020)
Today, ubiquitous devices typically can be associated with two important sides in the context of offering online business. Although one side brings lot of potential in terms of reaching end-users, the other side mounts up huge number of threatens to them through malware. Particularly, Android mobile phones now symbolize an idyllic option for malware developers. This paper proposes a behavior based approach for detecting and preventing malicious activities of the processes inside an application to be installed in Android devices. In order to appraise our system, we have taken testing data that consists of both legitimate samples and malicious samples. The experimental analysis and practical results show that our system is more efficient in malware detection with high detection rate with minimal false positive.